INTERNATIONAL EXPERIENCE OF THE ECONOMIC SIMULATION SOFTWARE USAGE IN EDUCATION - Antoniuk, D. (Journal of Information Technologies in Education (ITE), 2016)
The article describes the research of foreign business simulation usage experience within courses of MBA programs, higher education institutions, as a part of scientific researches and also as a platform for competitions and championships. Development of the information and communication technologies that causes decrease of business simulation purchasing, development and support expenses, gives a chance to expect business simulations usage spreading and expanding to the other potential usage domains. Business simulation development and usage area dynamics enables to conduct tendencies analysis of the market and work out the hypothesis regarding potential new business simulations usage areas. Additionally, business simulation market leaders’ products and services development and adjustments observation is proved to be possible and necessary. Exact business simulations usage examples at the foreign higher education institutions and business schools are described. Systematization of the studied and described business simulations has been performed. Besides, business simulations are proved to be effective for complementing traditional teaching methods and supporting the different domain specialists’ economic competencies development. Foreign experience of the business simulation usage may help to build the basement for the implementation of this learning and scientific research tool at the educational and scientific institution in Ukraine.